Impacts of copper and lead exposure on prokaryotic communities from contaminated contrasted coastal seawaters: the influence of previous metal exposure. Issue 6 (19th March 2020) - Coclet, Clément; Garnier, Cédric; Durrieu, Gaël; D'onofrio, Sébastien; Layglon, Nicolas; Briand, Jean-François; Misson, Benjamin
ABSTRACT: Our understanding of environmental factors controlling prokaryotic community is largely hampered by the large environmental variability across spatial scales (e.g. trace metal contamination, nutrient enrichment and physicochemical variations) and the broad diversity of bacterial pre-exposure to environmental factors. In this article, we investigated the specific influence of copper (Cu) and lead (Pb) on prokaryotic communities from the uncontaminated site, using mesocosm experiments. In addition, we studied how pre-exposure (i.e. life history) affects communities, with reference to previous metal exposure on the response of three prokaryotic communities to similar Cu exposition. This study showed a stronger influence of Cu contamination than Pb contamination on prokaryotic diversity and structure. We identified 12 and 34 bacterial families and genera, respectively, contributing to the significant differences observed in community structure between control and spiked conditions. Taken altogether, our results point toward a combination of direct negative responses to Cu contamination and indirect responses mediated by interaction with phytoplankton. These identified responses were largely conditioned by the previous exposure of community to contaminants. Abstract : Impacts of copper on prokaryotic communities depend on metal exposure history.